From Biden to Trump: Waning Turkish-American relationship demands greater European engagement - Mehmet Yegin; Salim Çevik (Stiftung Wissenschaft und Politik (SWP), 2024)
President Biden's term is coming to an end. Turkish-American relations have reached a low, with Erdoægan noting that Biden is the first US president with whom he has had no meaningful dialogue. The Erdoægan government believes this is due to the Biden administration's "overemphasis" on democracy and human rights, and hopes that election of Donald Trump will open a new page. However, the bilateral problems are deeper than Erdoægan realises and relations will remain at a low level for the foreseeable future. Turkey's strategic importance to the United States is in decline not only because of Washington's "pivot to Asia", but also due to Erdoægan's considerable liabilities, his waning political credibility, and diverging interests between Ankara and Washington in the region. This steady downturn has direct implications for the European Union, which does not have the luxury of downgrading its engagement and will have to take the lead.
Keywords: 320; Turkey; United States; EU; Joe Biden; Recep Tayyip Erdoægan; Xi Jinping; Ursula von der Leyen; People's Defence Units (YPG); Kurdistan Workers Party (PKK); Syrian Democratic Forces (SDF); S-400s; F 35 warplanes